2008
DOI: 10.1002/pen.21074
|View full text |Cite
|
Sign up to set email alerts
|

Rheological properties, flow visualization and extrudate swell of NR compound by rotating‐die rheometer

Abstract: An experimental apparatus coupled with a rotating die system was especially designed and manufactured to study the rheological properties, flow patterns and swelling behavior of natural rubber (NR) compound for different shear rates and die rotating speeds at a test temperature of 1108C, the results being compared with those by the static capillary die. It was found that NR compound used exhibited psuedoplastic non-Newtonian behavior. The rotation of the capillary die could reduce the extrusion load. The wall … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 23 publications
0
18
0
Order By: Relevance
“…At the same shear rate, it was found that the difference in shear stress of both types of NR compound was no more than 4.5%. It could be concluded that a mixture with TiO 2 did not affect overall flow property of NR compound [16] . Results from the measurement of flow property indicated that the wall shear stress from divergent annular die was higher than the wall shear stress from convergent annular die by an average of 6.5 % at every shear rate.…”
Section: Measurements Of the Extrudate Swell Ratiomentioning
confidence: 90%
See 3 more Smart Citations
“…At the same shear rate, it was found that the difference in shear stress of both types of NR compound was no more than 4.5%. It could be concluded that a mixture with TiO 2 did not affect overall flow property of NR compound [16] . Results from the measurement of flow property indicated that the wall shear stress from divergent annular die was higher than the wall shear stress from convergent annular die by an average of 6.5 % at every shear rate.…”
Section: Measurements Of the Extrudate Swell Ratiomentioning
confidence: 90%
“…The formulation of the NR compound was shown in Table 1. The materials were compounded in accordance with the experimental procedure by Intawong et al [16] . The compound was divided into two separate parts, one of which was pigmented with titanium oxide (TiO 2 ) to create a white compound.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Figure 1b shows a cross-section of annular die that is assembled to a split barrel of the capillary rheometer, where the annular die is centrally fixed at the bottom of the barrel with a Die holder. In addition, a pressure transducer (Dynisco, Model PT460E-2CB-6, Franklin, MA) [10,11] is also installed on the 5mm top of the die entrance, in order to measure die entrance pressure drop, which will be further used to study the rheological properties.…”
Section: Experimental Technique and Apparatusmentioning
confidence: 99%